Atomic awakening : a new look at the history and future of nuclear power - Mahaffey, James A. (New York : Pegasus Books, 2009)
Evaluates the potential of nuclear technology as a non-polluting, renewable energy source while describing how nuclear energy's negative association with weapons development and the Cold War has stymied the progress of its beneficial uses.
The paradox inside a puzzle inside a fantasy -- 1: The fantasy -- Invisible demons -- A couple of remaining questions -- Einstein drops a bomb -- The other end of the universe -- Breaking open the atom -- 2: The puzzle -- A fortuitous condensation of genius -- An implied threat from the Fatherland -- A jolt in the dark -- A light at the mouth of the tunnel -- Post-war planning -- 3: The paradox -- A quest for power -- Digging canals, curing cancer, and flying to Jupiter -- The graphite's on fire! -- Nuclear rockets and nuclear airplanes -- The building boom, the bust, and a resurgence -- The radioactive park.
Includes bibliographical references and index.
1 2
Keywords: Nuclear engineering; Nuclear energy